IDENTITAS DAN NILAI DI DALAM NARASI-NARASI DOMINAN PERANG RUSIA - UKRAINA TAHUN 2022 - Muhammad Adhitama Nasrah, (2024)
On February 24, 2022, Russia invaded Ukraine. It begins with president Putin announcing the start of a "special military operation". In this war, many narratives were used to support the war interests of each side. This research aims to identify what narratives are dominant and reported by the media regarding the Russia-Ukraine War in 2022 and dig deeper into the identities and values contained in them. The research method is to use coding techniques to find out the big picture about the various narratives in this war. The data sources used are news from international media, Ukrainian media and Russian media. Furthermore, this research uses a constructivist approach to see the relationship between dominant narratives contained in various media and the identities contained in them to build collective identity, build the country's image, influence public opinion, and justify what they do in order to fulfill war interests.